Hardboiled - Yoshimoto, Banana 1964- (Grove Press, 2005)
Presents two novellas, one about a young woman's dream about an ex-lover while on a hiking trip, and the other about the sister of a woman lying in a coma.
Enth. ausserdem: Hard luck
Keywords: Japan -- Fiction